VIABILIDADE ECONÔMICA NA PRODUÇÃO DE CANOLA PARA REGIÃO DOS CAMPOS GERAIS, PARANÁ - Mainardes, Eriton Luiz (2016)
This study aimed to analyze the economic feasibility in canola production (Brassica napus var oleifera) for the Campos Gerais region - PR. Therefore, was interviewed eight producers, and used information from four of them for economic analysis. The variables analyzed were: cost of production, economic analysis (hurdle rate, net present value, internal rate of return, payback, profitability index and profitability index), sensitivity analysis and vegetable oil costs. Compared to canola with wheat (Triticum aestivum) - to be the main crop in the autumn and winter period - and soybean (Glycine max) - by liquidity in the world market. It was concluded that despite the economic analysis indicates superior results of canola production compared to the wheat crop and vegetable oil production is more attractive financially than soybeans, the culture of canola is still insignificant in the region of Campos Gerais (PR). The producers interviewed pointed to limit the culture of expansion financing the limited crop; the incipient technical assistance; adaptations of agricultural machinery; reduced number of pesticides released into the culture in the state of Paraná; canola be host of the soybean white mold disease (Sclerotinia sclerotiorun); the production process - marketing the seed sale - be coordinated by private companies; variable productivity; transportation, processing and storage with smaller grains to other crops.